Growing up on the streets: research with and for young people on the streets, 2012-2016 - Blerk, Lorraine van (UK Data Service, 2020)
'Growing up on the streets' was a qualitative, longitudinal, participatory research project following the lives of street children and youth as they grow up on the streets of three African cities: Accra, Ghana; Bukavu, DRC and Harare, Zimbabwe. Street children and youth were participants and researchers alongside street work practitioners, UK academics, a UK charity and African NGOs. Funding came from Backstage Trust. The innovative research design was developed with street children and youth (aged 14-20), employing a capability (rather than vulnerability) approach to their lives. They defined the 10 capabilities which formed the framework for the project. The project won awards for its innovative approach and impact. The data (2478 interviews) provides unique insights into the patterns of young people’s daily lives on the street as they seek to create adult lives to value.